El valor de la actividad física: a multilevel approach to understanding and improving PA among Hispanic adults - Martinez, Javier Luis (My University, 2025)
Background: The Hispanic population is growing linearly across the United States, with approximately 65 million Hispanics in 2023. The cultural and economic opportunities associated with the growing Hispanic population emphasize the importance of reviewing Hispanic health. The Hispanic population is at an increased risk for adverse health effects due to increased obesity rates. These increasing rates are important to address due to the illnesses/disease associated with obesity. While there are several factors impacting obesity rates, the primary focus of this dissertation will be on physical activity (PA), which is defined as any type of bodily movement producing energy expenditure. Thus, the objective of this dissertation is to identify and understand the factors affecting PA within the Hispanic population that will assist in creating equitable opportunities for future PA promotion within the community. This dissertation is comprised of three studies that outline specific goals in addressing the overall aim of the dissertation. Methods: The first study was a scoping review including literature within a 10-year period (2012-2022), which reviewed existing intervention programs aimed at improving PA within the Hispanic community. The strategies used in these programs were organized using the Social Ecological Model (SEM) to better understand the common levels that have been addressed within the ten-year time frame. The second study focused on the factors affecting PA among working Hispanic women (n=223). Quantitative data was collected among this population across the nation through a validated survey distributed by the Prolific database. This survey identified influences and barriers towards PA, which were categorized using the SEM. One-way ANOVA analysis and hierarchical linear regression were used to evaluate associations between PA levels and factors across SEM levels among working Hispanic women. The final study utilized a qualitative approach to expand upon PA influences among working Hispanic mothers. The incorporation of a collaborative research approach using Photovoice provided a wholistic approach to identifying the factors influencing PA. Results: The scoping review identified three components: the types of PA interventions addressing PA among low-income Hispanic populations, the most common levels of the SEM that have been targeted in PA interventions, and changes in PA among the Hispanic community. The scoping review included 14 intervention studies that included both short and long-term intervention programs (4 weeks-12 months). In-person and online interventions were used among the Hispanic population. The scoping review also identified the individual, interpersonal, and community levels of the SEM as the primary levels being addressed by the intervention programs. The one-way analysis revealed higher individual level factors (self-efficacy (F (2,220) = 10.00, p<.001), exercise planning (F (2,218) =14.33, p<.001), goal setting (F (2,218) =7.79, p<.001), and outcome expectations (F (2,219) = 4.30, p=.015)) among more active participants. Social support levels from family (F (2,218) = 6.06, p=.003) and friends (F (2, 219) =9.17, p<.001) were expressed by more active participants. In addition, work hours also differed among participants (F (2, 219) =3.46, p=.033), such that participants with higher activity were working more hours/week. The community level demonstrated an inverse relationship with PA when addressing crime (F (2,219) =5.64, p=.004). The least physically active participants reported the highest levels of crime in their neighborhood. The final two levels of organization and policy did not reveal any significant differences by PA level. The hierarchical linear regression demonstrated comparable results as individual level factors (R²=.059, p=0.001) and work hours demonstrated positive associations with PA (p=.024)., while crime was negatively associated (p=.024). The third study of the dissertation revealed key factors influencing PA participation among working Hispanic mothers through each level of the SEM. The individual level barriers were PA knowledge, time, and exhaustion. The facilitators for PA within the same level were categorized into intrinsic and extrinsic motivation. The interpersonal level categorized family and friends as both barriers and facilitators, depending on the positive or negative influence their social environment had on PA promotion. Pets were another social influence mentioned by the participants. Similarly, safety and physical environment were expressed as both facilitators and barriers within the community level. The structure and perception of safety within their surroundings impacted their decision on PA engagement. Culture was an emphasized inhibitor to PA due to the pressure of family obligation within the Hispanic culture. The organization level mentioned colleagues as both positive and negative influences on PA, while most participants expressed a supportive atmosphere for PA from their supervisors. The time commitment from occupations was another detrimental factor for PA. The policy level of the SEM is limited to a few policy initiative programs aimed at promoting PA promotion among the working Hispanic mothers, while many expressed the absence of PA opportunities through policies as an inhibitor to engaging in PA. Conclusion: Identifying subgroups within the Hispanic population that exhibit low rates of PA can assist in identifying the factors influencing PA participation. The incorporation of the SEM assisted in organizing the facilitators and barriers across distinct populations within the Hispanic community. The data collected within this dissertation can create a solid foundation for structuring future intervention programs with the factors identified in existing literature, as well as the factors identified by the studied population. While the data collected can create positive strides towards PA opportunities within the Hispanic community, future research can assist in addressing the higher levels of the SEM to provide intervention programs incorporating a wholistic approach necessary to create applicable programming among the entire Hispanic population.
Keywords: Physical activity; Hispanic